Feasibility of Reuse in the Concrete Industry - Al-Faesly, Zaineb (Université d'Ottawa / University of Ottawa, 2022)
The construction and demolition (C&D) waste produced by the Canadian construction industry accounts for 27% of the total municipal solid waste disposed in landfills. However, more than 75% of C&D waste has residual value and, consequently, could be salvaged, recycled, and/or reused. The need for comprehensive and integrated waste management mechanisms, technologies, rating systems, and policies is widely recognized. A waste management hierarchy tool exists for reducing and managing waste that follows this order: preventing, minimizing, reusing, recycling, energy recovering, and finally, disposing of the waste. It appears that the highest level attained by the concrete industry in Canada is recycling (e.g., crushing concrete and using it as base aggregate). This study aims to explore the opportunities and barriers to advance to the next level in the waste management hierarchy by reclaiming concrete from decommissioned structures for reuse with minimal reprocessing. A survey was distributed to members of the Canadian concrete industry to answer two main sets of questions: 1) to what degree, if any, is the Canadian construction industry currently reclaiming waste concrete by recycling and/or reusing it? and 2) what is the perception of industry professionals on concrete reuse? What are the perceived benefits and challenges of such a practice? A total of 125 participants responded to the survey. Although the environmental advantages of concrete reuse were clear to all, views on the financial benefits were mixed. Many participants highlighted that a successful approach to concrete reuse should involve all parties and stakeholders. Overall, there is positive interest in the concept of concrete reuse; however, there is apparent uncertainty on how to approach it and, thus, there is a need for practical guidance to address various technical, logistical, and liability concerns in a comprehensive and holistic manner. Two cases studies – one for a bridge and one for a building – were developed to address some of the technical challenges associated with reusing concrete in structural applications. The case studies were based on local existing structures that were hypothetically disassembled then repurposed in conceptual redesigns. The design of connections to effectively recouple the deconstructed structural components was a focal, and challenging, aspect of the case studies; in support of shifting towards a circular economy, the connection designs were engineered to be reversible to facilitate future adaptation and/or further dismantlement. It is important to highlight that a desirable reuse project starts in the initial design phase, where the ultimate disassembly and repurposing of the structure is considered from the start (i.e., cradle to cradle design). However, since this is presently not mainstream practice, these case studies focus on the more complex task of deconstructing existing structures that were not designed with the intention of reuse. Although several challenges were encountered, this approach is an essential first step in the present framework to move the discussion forward in the context of reuse of structural concrete members.
Keywords: Concrete reuse; Building disassembly; Building repurposing; Reversible design; Cradle-to-cradle design; Sustainable design; Circular economy; Industrial ecosystem; Construction waste; Waste management; Demolition waste